Effect of two dose level f FSH on superovulatory response, total and viable embryo recovery in Holstein Friesian x Sahiwal crossbred cows with repeated flushing - PATEL, D V; SINGH, S P; NIKHATE, R V; PANCHAL, A G; KASIRAJ, R (The Indian Journal of Animal Reproduction, 2007)
The Holstein Friesian x Sahiwal (HF x S) donor cows were selected randomly and distributed in to two groups (A&B). A total of 32 & 42 embryo flushings in group A & B respectively were performed superovulation was achieved by treatment with 200 mg FSH in group A and 400 mg FSH, in group B. the schedule comprised of 8 equal doses between day 9 and 11 post estrus ( day O is day of standing estrus). Estrus was induced by injecting single dose of Prostaglandin F2a 48 hr. from first FSH injection. Artificial insemination (AI) was carried out with frozen semen on day 7 post estrous. Donors were flushed non surgically and revealed no embryo recovery in 5 animals (15 .63%) of group A and 7 animals (16.67%) of group B. The analysis was done-with respect to dose regimen (50% Vs 100%) and repeated flushings (1’1, 2nd and 3rd flush) within the group and between the groups. The mean of ovulation, anovulatory follicles, and viable embryo recovery (VE) with respect to the two FSH regimen revealed no significant difference (P<0.05). With regard to the repeated flushings in A group, there was significant reduction in total embryo recovery (TE) in l st and 3rd flush, while as there was no difference in other parameters within the group. Similarly in B group, there was a significant reduction in VE in I st and 3rd flush, while there was no difference in other parameters within the group. Comparing the differences in I st, 2nd and 3rd flushing ofboth groups, there was no significant difference in all parameters. It was concluded that the cost of flushing can be reduced in HF x S donors through reduction in dose ofFSH without affecting the results.